অপ্রস্তুত কলাম - সায়ীদ, আবদুল্লাহ আবু (ঢাকা : সময় প্রকাশন, 2008)
Articles chiefly on social and governance issues of Bangladesh.
In Bengali.
Keywords: Bangladesh -- Social conditions; Bangladesh -- Politics and government -- 1971-